Sprouted pumpkin seed flour: Physical, physical-chemical and colorimetric aspects (Research, Society and Development, 2021)
The pumpkin (Cucurbita moschata) is a vegetable appreciated by people of all income levels, however, its seeds are discarded, characterizing a waste due to its rich nutritional composition. One of the ways to minimize this disposal is to provide alternatives for using the seed, increasing its attractiveness for industrialization and consequently the possibilities of its application in the preparation of food for human consumption. Thus, the objective was to evaluate the physical, physico-chemical and colorimetric characteristics of fresh, germinated pumpkin seeds and the flour of germinated pumpkin seeds. The samples were characterized in terms of unit specific density, real and apparent, porosity, color, volume, length, width, thickness, circularity, sphericity, water content, water activity, pH, total titratable acidity, ash, lipids, proteins, total and reducing sugars, it was also determined the moisture adsorption isotherms of dry flours at temperatures of 20, 25 and 30º C. It was found that the Peleg model, followed by the Oswin model, were the ones that presented the best adjustments to experimental data Germination changed the unit mass, porosity, colorimetric parameters and generated a considerable increase in protein content. The drying caused transformations in the unit mass, porosity, circularity and sphericity. As for the physical-chemical parameters, there was a reduction in pH and reducing sugars and an increase in the levels of lipids and proteins. Thus, the germinated pumpkin seed flour showed good results, mainly in relation to the protein content, presenting itself as a good alternative for the development of new products.